UNDERSTANDING THE ONLINE MOVEMENT FOR #HARIPRABANGSANASIONAL - Amida Yusriana; Nurul Hasfi; Sunarto Sunarto; Luz Rimban (Universitas Bunda Mulia, 2021)
Hari Prabangsa Nasional with hashtag (#) symbol had took over twitter during early February 2019. This trending topic was popularized by AJI Indonesia to protest against the government’s policy that has the possibility of threatening the press freedom. Prabangsa is the name of a journalist that was murdered by I Nyoman Susrama. This movement arised because of the policy to grant remission to the murderer. Hari Prabangsa Nasional or shortened as HPN has the similar abbreviation to Hari Pers Nasional (HPN). The aim of this research is to understand how Twitter as social media is employed as the new form of the press freedom protest. This research will be analyzed by The Logic of Connective Action Theory by Bennett and Segerberg . The Logic of Connective Action Theory argues for a more expansive path to concerted actions through the selfmotivated sharing of personalized content on social media. This research uses the Critical Discourse Analysis Method. This method will analyze the phenomenon from three different levels, such as the producer of social movement, the twitter text and the consumer of the social movement. The merit of this research is to add depiction that social media is effective way for conducting a social movement. The finding shows that to employ the Twitter for such movement, offline and online combination are still needed.